2019
DOI: 10.1371/journal.pone.0221827
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis of six chloroplast genomes from three Persea americana ecological races: Insights into sequence divergences and phylogenetic relationships

Abstract: Chloroplasts significantly influence species phylogenies because of their maternal inheritance and the moderate evolutionary rate of their genomes. Avocado, which is a member of the family Lauraceae, has received considerable attention from botanists, likely because of its position as a basal angiosperm. However, there is relatively little avocado genomic information currently available. In this study, six complete avocado chloroplast genomes from three ecological races were assembled to examine the sequence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
4
15
0
Order By: Relevance
“…), which is a member of the family Lauraceae of the order Laurales, is one of the most economically important subtropical/tropical fruit crops worldwide [1][2][3]. Avocado is a highly diverse species with local variations that have resulted in various ecological races [4]. Additionally, it is native to Meso-America, but the 'subtropical' ecotypes (Guatemalan and Mexican) are currently widely grown in countries and regions with warm-to-cool subtropical and Mediterranean climates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), which is a member of the family Lauraceae of the order Laurales, is one of the most economically important subtropical/tropical fruit crops worldwide [1][2][3]. Avocado is a highly diverse species with local variations that have resulted in various ecological races [4]. Additionally, it is native to Meso-America, but the 'subtropical' ecotypes (Guatemalan and Mexican) are currently widely grown in countries and regions with warm-to-cool subtropical and Mediterranean climates.…”
Section: Introductionmentioning
confidence: 99%
“…Number of observed alleles, 2 effective number of alleles,3 observed heterozygosity,4 expected heterozygosity, and5 Shannon's information index.…”
mentioning
confidence: 99%
“…With the increased application of high-throughput sequencing technology, the number of characterized chloroplast genomes of angiosperms is increasing rapidly 55 . In this study, we found that the two newly sequenced Gleditsia species have similar quadripartite structure and gene contents to the published chloroplast genomes of other members of the Caesalpinioideae sub-family 15 , 56 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional methods, DNA barcoding can be applied to accurately identify G. sinensi s and its adulterant, G. japonica . DNA barcodes refer to relatively short fragments of DNA with substantial genetic variation, which can be standardized, easily amplified, and representative 55 . DNA degradation frequently occurs during the production of natural medicine, which can decrease the efficiency of PCR 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic characterizations providing tangential signals of horticultural races have used targeted genes (Chen et al, 2009), cpDNA (Ge et al, 2019), SSR (Alcaraz and Hormaza, 2007;Ferrer-Pereira et al, 2017;Boza et al, 2018;Sánchez-González et al, 2020) and SNP markers (Kuhn et al, 2019c;Rubinstein et al, 2019;Talavera et al, 2019), in some cases using gene-bank accessions, like from the Venezuelan germplasm bank (INIA-CENIAP) (Ferrer-Pereira et al, 2017), the National Germplasm Repository (SHRS ARS USDA) in Miami (Kuhn et al, 2019a;Kuhn et al, 2019b), and the Spanish germplasm bank (Talavera et al, 2019). Despite some of these analyses captured all three races (Talavera et al, 2019), others exhibited mixed and inconclusive population structure (Cañas-Gutiérrez et al, 2015;Cañas-Gutiérrez et al, 2019;Cañas-Gutierrez et al, 2019).…”
Section: N R E V I E Wmentioning
confidence: 99%